Representation of salt solubility in mixed solvents: a comparison of thermodynamic models - Pinho, Simão (2010)
A simple and accurate apparatus for the measurement of salt solubilities in mixed solvents by an analytical method is presented. Salt solubility data have been measured for the systems water/methanol/NaCl, water/methanol/KCl at 298.15 and 323.15 K and for the system water/ethanol/NaCl at 298.15, 323.15 and 348.15K.